PEMBANGUNAN DIGESTER GASBIO GUNA MENANGGULANGI GEJOLAK SOSIAL MASYARAKAT SUKODONO SIDOARJO - Yuwono, Istantyo; Sidqon, Moch. (Fakultas Teknik Universitas 17 Agustus 1945 Surabaya, 2014)
The unpleasant smell of dung fly everywhere, dirt strewn everywhere be a factor for the emergence of social conflict surrounding of cow breeding. Biogas digester in the form of a closed tube can be used for cow dung that is no longer scattered and the scent is not pleasant been isolated. Not only that bio-gas produced can be used together with the communities around the farm, which in turn not only relieve social turmoil but rather strengthen the social fabric. Now they jointly maintain and care for the sake of expediency digester together. Bio-gas digester constructed is fixed dome models (fixed dome) with capacities of 10 m3 of manure. It means being able to accommodate dirt 10-15 cow. After 60 days of curing in the tube digester, biogas digester turns is able to produce enough gas used for cooking purposes 15 families around the farm together.Keywords: digester, biogas, cow breeding, social conflict